Palliative Care in the Hip Fracture Patient - Sullivan, Nicole M. (Geriatr Orthop Surg Rehabil, 2019)
INTRODUCTION: Older patients with hip fracture have a 20% to 30% mortality rate in the year after surgery. Nonoperative care has higher 1-year mortality rates and is generally only pursued in those with an extraordinarily high surgical risk. As the population ages, more patients with hip fracture may fall into this category. The orthopedic surgeon is typically the main consultant responsible for deciding between surgery and conservative management, and the reasoning behind one decision over the other is often poorly understood. We undertook a review to determine decision-making tools for surgery in high-risk patients with hip fracture. MATERIALS AND METHODS: A review was conducted using PubMed to determine articles published using the terms palliative care, conservative care, nonoperative, hip fracture, orthopedic procedures, fracture fixation, and surgery. Our search resulted in 13 articles to review. These were further screened to determine tools for use in surgical decision-making. RESULTS: Several potential decision-making tools were found in our search. The potential tools to identify patients who would benefit from nonoperative treatment included the Palliative Performance Scale for severe dementia, the Lawton Instrumental Activities of Daily Living and Katz Activities of Daily Living scales for prefracture immobility, a combination of clinical signs and laboratory tests to determine risk of imminent death, and the Charlson Comorbidity Score for additional serious comorbidities. No tools have been prospectively tested in a clinical setting. DISCUSSION: Evaluation of each patient using a variety of decision making tools should help the orthopedic surgeon determine which patients would be better suited to non-operative management. After determining the benefit of non-operative care, they must effectively allow the fracture to heal while ameliorating pain. Palliative care physicians can fulfill this role by providing support and symptom relief. CONCLUSIONS: Surgical decision-making for hip fracture repair in the elderly patients is not straight forward. Several tools may be helpful to the surgeon in determining who may be better suited for nonoperative care or a palliative care referral. Prospective data do not exist in these decision-making tools.